Sustainable career transitions and mental health support in elite sport: a systematic review of evidence and practices - Di Rocco, F.; Romagnoli, C.; Ciaccioni, S.; Capranica, L.; Padua, E.; Guidotti, F. (Sports, 2025)
The present systematic review aims to provide a comprehensive synthesis of evidence and practices regarding sustainable career transitions in elite sport. Following PRISMA guidelines, an extensive literature search was conducted in SPORTDiscus (EBSCOhost), PsycINFO, Scopus, Web of Science, and Google Scholar databases, resulting in 117 manuscripts, published from January 2015 to May 2025, and meeting the defined inclusion criteria. The review focused on mental health, dual-career pathways, transition readiness, and identity-related issues among elite athletes, Olympians, and Paralympians. Methodologies included qualitative, quantitative, and mixed-methods designs, with multisport and mixed-gender samples prevailing. The most commonly used instruments were semi-structured interviews and surveys. The main findings highlighted the centrality of mental health support, the role of dual-career planning, and the importance of proactive identity negotiation. Despite growing research interest, significant gaps persist in access to psychological support, structured transition planning, and dual-career strategies, with notable inconsistencies across countries and sports. The review emphasizes the necessity for integrated, multidimensional guidance, culturally sensitive psychological services, and flexible educational pathways to promote athlete well-being and sustainable post-sport careers. These insights are intended to inform the implementation of the ERASMUS+ funded PORTAL project, supporting evidence-based interventions and the development of resources such as an online platform and Real-Life Transition Officers to enhance the transition experiences of elite athletes.